ANALYSIS OF WAR CRIMES IN THE 2022 RUSSIAN-UKRAINIAN ARMED CONFLICT ACCORDING TO INTERNATIONAL HUMANITARIAN LAW - Fathia Firdaus (Mediasi: Journal of International Relations, 2022)
This study aims to analyze the war crimes that occurred in the Russia-Ukraine conflict in2022. The conflict that began with a military operation carried out by Russia in early 2022was Russia's attempt to stop Ukraine from joining NATO and to protect its country from theinfluence of NATO and the European Union. If Ukraine joins NATO, the direct barrierbetween Russia and the West will disappear. Russia also has the potential to lose severalborder areas that can affect the country's geopolitics. In that conflict, some acts wereconsidered war crimes and violations of the laws of war. This study uses qualitative researchmethods with descriptive data. The results of this study indicate that a series of violationsconstituting war crimes have occurred in the conflict between Russia and Ukraine. The formsof crimes that occurred were attacks on infrastructure buildings such as hospitals, theatres,schools, train stations, and power plants, as well as torture, murder, and sexual violenceagainst civilians. The attacks launched and the many victims in the conflict show that therehave been violations of article 50 of the Geneva Convention I, articles 3 and 27 of the GenevaConvention 4, article 51 of the Additional Protocol, and article 8 of the Rome Statute. Amongthe series of violations that occurred in the conflict, many were committed by the Russianarmy, but some were committed by the Ukrainian army. In some of the attacks that have hitcivilians, Russia and Ukraine have blamed each other for the attacks.